The perverse economy : - Perelman, Michael (Palgrave Macmillan, 2003)
From Adam Smith to the present day, economic theory has shortchanged the workers most crucial to the functioning of human life and offered skewed views of scarcity and extraction. Perelman shows how this approach has produced a discipline in which its followers' models and representations of the world around them are so removed from reality that continuing to abide by them would jeopardize both human capacities and nature itself.